Translating Hand Expressions in the Holy Qur’an: (An Analytical - Semantic Study) - Ibraheem, Anas Khalid (Al-Adab Journal, 2021)
Translators have long been regarding the translating of the Holy Qur’an as a polemic job. The vast majority of Muslim scholars and conservatives were objecting to any translation due to its holiness. Now, when the word translation replaced by interpretation as a norm to people, they start accepting the idea that there is a need for those who are non-Muslims or Arabs. Yet, this does not tolerate the fact that it is hard to endure for many reasons; of which its sacredness, cultural impact, linguistics inimitability, and its vivid metaphorical language. The problem of translating such a rhetorical language, which is rich of metaphorical styles, is perhaps the ultimate task for any translator. Hand expressions which are metaphorically embodying Allah (God) is a whole different problem. How to translate it? When to translate it? Is it acceptable? Do we keep it or change it into more sensible words? All these questions must be kept in mind while translating. This paper tries to answer these questions by studying "hand expressions" and its metaphorical images, analyzing the kinds of metaphor and the strategies used in the process of translation. For this purpose, three translated versions and from different periods belonging to translators having different backgrounds are examined. After analyzing the collected data, the results show how each version has translated the metaphorical images of hand expressions, the adopted kinds of metaphor, the strategies used, and how each one managed to do so and why.